THE EFFECTS OF EARLY EXTIRPATION OF THE THYMUS IN ALBINO RATS - Pappenheimer, Alwin M. (The Rockefeller University Press, 1914)
It has been shown that white rats may survive complete extirpation of the thymus for at least 131 days, even when the operation is performed within the first two weeks of life. Removal of the thymus does not produce an arrest or retardation of body growth and development. Qualitative changes in the skeletal system or teeth have not been found. In emaciated, weak animals osteogenesis is less active than in healthy rats, and the long bones are smaller and more delicate in structure. Such quantitative differences appear to depend upon the general nutrition, are equally pronounced in rats whose development is retarded from other causes, and cannot be referred specifically to loss of thymus function. No constant or characteristic alterations were detected in the spleen, testes, adrenals, or thyroid. Whatever functional correlations may exist between thymus and any or all of these organs are not evident from the occurrence of histological changes after the removal of the thymus. The relative proportion of lymphocytes in the blood is diminished for the first few weeks after the operation. We have not determined how long this alteration in the leucocytic formula persists. Since this paper went to press an article has appeared by Klose, describing briefly the results of thymus extirpation in pigs, goats, rats, and chickens. In rats thymectomized on the fourteenth day, there followed a progressive cachexia terminating in death after eight to ten weeks. Disturbances in ossification, which macroscopically and microscopically were identical with those of human rickets, developed also in the ribs and long bones. Some of Klose's litters failed to show these lesions, and this negative result is explained as having been due to the presence of thymic tissue within the thyroid gland. The observations of Klose are in direct contradiction to the negative results described in this paper. Since the possible presence of accessory thymus tissue either within the thyroid or elsewhere was carefully excluded in my experiments, the discrepancy between my findings and those of Klose cannot be explained upon this basis. Since this paper was sent to the publisher I have studied two additional rats which were killed 185 days after operation. Minute examination of a complete series of the neck organs, including the thyroid, failed to show any tissue which could be interpreted as thymus. The bones showed no rachitic changes. The infective origin of rachitic and osteomalacic lesions in rats has been established by Morpurgo. Although reference is made by Klose to Morpurgo's work, the data given by him do not enable one to judge whether this infection was definitely excluded.